Peranan Teknologi Informasi Dan Komunikasi Untuk Meningkatkan Interaksi Efektif Dalam Pembelajaran - Rani Simanjuntak; Cindy Aritonang; Aman Simaremare; Elya Siska Angraini (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Information and Communication Technology (ICT) plays an important role in the world of education today, especially in the learning process. This research aims to review the role of ICT in increasing effective interaction in learning through library research methods. A qualitative approach is used with a focus on analyzing relevant scientific literature from various sources such as academic journals, books, review articles, and other online sources. The results of the analysis show that ICT provides opportunities to present learning material in an interactive and interesting way, improve communication and collaboration, personalize learning, support distance learning, and increase student learning motivation. However, challenges such as limited access, teacher skills and parent involvement need to be overcome. Suggested solutions include providing adequate ICT infrastructure, training for teachers, and education for parents. By paying attention to these factors, ICT can be an effective tool for increasing interaction in learning and improving the overall quality of education. The integrity of the use of ICT in the learning process will help create a conducive and enjoyable learning environment for all students.